Proportion of Amotivation Learning Students Who Work and do not Work on Academic Achievement - Fany Della Utari; Ardhita Eko Ginanjar (Journal of Psychology and Culture Behavior in SDGs, 2025)
Objective: This research aims to analyse the differences in Grade Point Average (GPA) between students who study while working and those who do not, their level of amotivation, and the interaction of employment status with amotivation among economics education students at Universitas Negeri Surabaya. Method: This research is a comparative quantitative study using simple random sampling on economics education students from the fifth to the seventh semester, with a total of 177 students. The analysis technique uses Chi-Square and Odds Ratio with the assistance of SPSS software. Results: Research results indicate that there is no difference in the proportion of academic achievement risk between students who work and those who do not. However, there is a difference in the proportion of risk to academic achievement between students with high and low levels of amotivation. Students with high amotivation are more likely to experience a decline in academic achievement. Meanwhile, no difference was found in the proportion of risk to academic achievement between students who work and have high amotivation and students who do not work and have low amotivation. These findings suggest that the amotivation factor has a stronger influence on academic achievement than whether or not a student works. Novelty: The combination of two contexts, namely the employment status of students and amotivation towards academic achievement, represents a conceptual innovation and focuses on economics education students who have never been studied before. This provides a broader contribution.